Oxychlorination–Dehydrochlorination Chemistry on Bifunctional Ceria Catalysts for Intensified Vinyl Chloride Production. (28th January 2016) - Scharfe, Matthias; Lira‐Parada, Pedro A.; Paunović, Vladimir; Moser, Maximilian; Amrute, Amol P.; Pérez‐Ramírez, Javier
Abstract: Ceria catalyzes the one‐step production of the vinyl chloride monomer (VCM) from ethylene with a high yield because of its bifunctional character: redox centers oxychlorinate ethylene to ethylene dichloride (EDC), which is subsequently dehydrochlorinated to VCM over strong acid sites generated in situ. Nanocrystalline CeO2 and CeO2 ‐ZrO2 lead to a VCM yield of 25 % in a single pass, outperforming the best reported systems and reaching industrially attractive levels. The use of CeO2 intensifies the current two‐step process within PVC production encompassing CuCl2 ‐catalyzed oxychlorination and thermal cracking. In addition, ceria‐based materials offer stability advantages with respect to the archetypical CuCl2 ‐based catalysts.